Contribution of Entertainment Tax to Original Regional Income Revenue in Pangkajene and Islands Regency - Muhammad Fadli (Pustaka Digital Indonesia, 2023)
This research investigates the contribution of entertainment tax to the local revenue of Pangkajene and Islands Regency, aiming to assess the significance of this revenue source and explore government efforts to enhance its contribution. Utilizing quantitative descriptive analysis, data was collected through field research, library research, and interviews. The findings indicate a fluctuating trend in entertainment tax contributions from 2018 to 2022, with a noticeable increase from 2020 to 2022 after a prior decline. Despite this rise, the average contribution remains relatively low. The study identifies obstacles, including taxpayer awareness, high tax rates, and the impact of the COVID-19 pandemic on entertainment tax revenues. The research emphasizes the importance of optimizing the mapping of local revenue potential and suggests strategies for the regional government to enhance entertainment tax income. Efforts such as surveys, intensified tax apparatus teams, and exploring new potential sources are recommended. In conclusion, while there has been improvement, the effectiveness of entertainment tax revenue remains categorized as